Potensi Wisata Pantai Muaro Sasak di Kabupaten Pasaman Barat Menjadi Daya Tarik Wisata Ditinjau dari Komponen 4a - Silvia Susanti; Pepy Afrilian M.Par (i-Tourism: Jurnal Pariwisata Syariah, 2023)
The main problem in this thesis is how the tourism potential of Muaro Sasak Beach becomes a tourist attraction in terms of the 4A component of tourist destinations, namely Attractions, Access, Supporting Facilities and Supporting Services. The purpose of this study was to determine the tourism potential of Muaro Sasak Beach, West Pasaman Regency, as a tourist attraction seen from the 4A components, namely Attraction, Accessibility (Access), Amenities (Supporting Facilities), and Ancillary Services (supporting services). The type of research used is field research with a descriptive qualitative approach. Data collection techniques that researchers use are: observation, interviews, and documentation. To test the validity of the data obtained in the field, the tringulagi source technique was used. Based on the results of research conducted by researchers in the field, it can be concluded that the Muaro Sasak Beach Tourism Object already has tourism potential by making Muaro Sasak Beach a tourism object, which has a positive impact on the economy of the surrounding community. In addition, this Muaro Sasak Beach Tourism Object has fulfilled the four components of tourism, in terms of attractions, this Muaro Sasak Beach tourist attraction has great potential because it already has natural attractions, cultural attractions, and man-made attractions and also in terms of access. Access to the Muaro Sasak Beach object consists of paved roads and transportation such as cars and motorbikes, this has explained that in terms of access to Muaro Sasak Beach, it has potential. Likewise, in terms of facilities, this Muaro Sasak Beach Tourism Object already has complete facilities such as: restaurants, stalls, places of worship, parking lots, trash cans, toilets, chendramata shops and others. Meanwhile, additional services at the Muaro Sasak Beach Tourism Object such as: security posts, health posts, banking services or BRI Link, internet networks already exist, although people still provide them. From the explanation above, additional facilities and services have the potential to become a tourist attraction.